Integrated Land Use Modelling for Assessing the Socio-Ecological Impacts of Regional Agricultural Land Use Change - Nishizawa, Takamasa; Justus Liebig University Giessen (My University, 2024)
Agriculture today is under increasing global land use pressure: to provide food efficiently while accounting for the ecological consequences of agricultural land uses. This thesis aims to identify prominent, regionally relevant land use drivers and assess their socio-ecological impacts on regional agricultural land use, considering land managers’ decision-making processes. To achieve this, an integrated land use impact assessment framework was developed to evaluate the socio-ecological impacts of land use changes in rural regions of Switzerland and Estonia. The results reveal that socioeconomic drivers, particularly agri-environmental schemes (AES), play a dominant role in agricultural land use in both study areas. Changes in agri-environmental payments (AEP) on land use were found to have a more pronounced impact on land use than other divers. To enhance farmland biodiversity, orchard meadows and semi-natural grasslands—both extensively managed—were identified as critical. However, financial support for these grassland types is essential, as they are unprofitable due to low productivity in terms of yields, forage quality, and labour efficiency. Nonetheless, increasing AEP for these grassland uses beyond the current level is likely to worsen the trade-offs: windfall profits rise and the cost-effectiveness of AES declines as more resources (e.g. land and labour) will be allocated to those less productive land uses. In conclusion, improving the profitability of extensively managed grassland management without increasing governmental budgets is a desirable strategy. This could be achieved by, for example, enhancing management efficiency to address labour shortages or by branding locally and ecologically produced grass-based products to create market opportunities for land managers. Yet, the Estonian case study suggests that purely demand-driven measures are insufficient to sustain extensive grassland use, as usage reserves in more intensively managed grasslands are prioritised and exploited first.